A profound analysis of Rb2[PH] and Cs2[PH] and the role of [PH]2- ions during temperature-induced solid–solid phase transitions - Somer, M.; Schnering, H. G. V.; Hochrein, O.; Zahn, Dirk (Solid State Communications, 2014)
The temperature-induced solid–solid transformation of Rb2[PH] and Cs2[PH] is characterized from both experiment and theory. Neutron diffraction, IR-spectroscopy and ab-initio molecular dynamics simulations reveal an asymmetric shift of the lattice constants at 80 K. The molecular mechanism of the structural transformation as identified from IR-spectroscopy and ab-initio molecular dynamics simulations is closely connected to the orientation of the [PH]2- moieties which undergo a partial order– disorder phase transition.
EAM Import::2019-03-13